Confession of Zina Offense in Aceh: Legal Awareness or Compulsion? - Ali Abubakar (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
AbstractThe purpose of this paper is to analyze the terminology of confession of guilt in the Qanun Jinayat Aceh, both material and formal law. This topic needs to be studied considering that Qanun Jinayat is seen as a new legal norm in Indonesia, which was adopted from a different legal system, namely Islamic jurisprudence. The difference in the source of this system gives rise to many problems with legal norms and their enforcement in cases. Research on the decisions of the Syar'iyah Court in Aceh in the adultery case; carried out using a normative juridical approach, by reviewing the Qanun viewed from legal norms, confession of guilt. The results of the study show that (1) juridically, confession gets an official place as special evidence for adultery; referring to the Koran; (2) the confession of guilt by the alleged perpetrators of adultery is influenced by the initial process of their arrest as the perpetrators of the crime; in part it may be an encouragement of the belief in obtaining forgiveness stemming from the Islamic religious doctrine that punishment in this world is a pardon and will abolish punishment in the hereafter; (3) the strategy of law enforcement officials does not play much role here because some of their duties have been "implemented" by the community which is understood as part of their legal awareness. AbstrakTujuan penulisan ini adalah untuk menganalisis terminologi pengakuan bersalah dalam Qanun Jinayat Aceh (QAHJ) baik hukum materil maupun formil. Topik ini perlu dikaji mengingat Qanun Jinayat dipandang sebagai sebuah norma perundang-undangan baru di Indonesia, yang diadopsi dari sistem hukum yang berbeda yaitu hukum Islam. Perbedaan sumber sistem ini melahirkan banyak problematika norma hukum dan penegakannya pada kasus-kasus. Penelitian atas putusan Mahkamah Syar`iyah di Aceh dalam perkara perzinaan; dilakukan menggunakan pendekatan yuridis normatif, dengan mengkaji Qanun yang dilihat dari norma hukum, pengakuan bersalah. Hasil penelitian menunjukkan bahwa (1) secara yuridis pengakuan mendapatkan tempat resmi sebagai alat bukti khusus zina; mengacu kepada al-Quran; (2) pengakuan bersalah oleh tersangka pelaku perzinaan dipengaruhi oleh proses awal penangkapan mereka sebagai pelaku kejahatan; sebagiannya mungkin merupakan dorongan keyakinan mendapatkan pengampunan yang berasal dari doktrin agama Islam bahwa hukuman di dunia merupakan sebuah pengampunan dan akan menghapuskan hukuman di akhirat; (3) strategi aparatur penegakan hukum  tidak banyak berperan di sini karena sebagian tugas mereka sudah “dilaksanakan” oleh masyarakat yang dipahami sebagai bagian dari kesadaran hukum mereka.